2007
DOI: 10.11606/rco.v1i1.34694
|View full text |Cite
|
Sign up to set email alerts
|

A concentração do controle acionário e a política de dividendos das empresas listadas na Bovespa: uma abordagem exploratória à luz da teoria de agência

Abstract: Este artigo busca, sob a perspectiva da Teoria de Agência e a partir de revisão bibliográfica, pesquisa empírica exploratória e investigações analíticas, verificar se a composição acionária das empresas brasileiras com ações negociadas na Bovespa, tem relação com a política de dividendos por elas adotada. Os resultados obtidos, por meio de testes estatísticos, sugerem a não rejeição da hipótese (H 0) elaborada neste trabalho. Verificou-se que um aumento na concentração acionária provoca um aumento no valor dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
1
11
0
5
Order By: Relevance
“…In such cases, the majority shareholder has greater power over the managers in the definition of dividends. A positive sign is anticipated (Dalmácio & Corrar, 2007).…”
Section: Table 1 Summary Of Factors That Influence Dividend Paymentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases, the majority shareholder has greater power over the managers in the definition of dividends. A positive sign is anticipated (Dalmácio & Corrar, 2007).…”
Section: Table 1 Summary Of Factors That Influence Dividend Paymentsmentioning
confidence: 99%
“…Such studies include Dalmatius and Corrar (2007), Setia-Atmaja, Tanewski, and Skully (2009), Jo and Pan (2009) and Holland and Coelho (2012). Dalmácio and Corrar (2007) Gompers, Ishii, and Metrick's (2003) G index of governance. They found that firms with entrenched managers are more likely to pay dividends and that doing so lowers cash holdings, thus rendering firms more vulnerable to hostile takeovers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the most important determinants of an enterprise's dividend policy were the level of current and expected future earnings and the pattern or continuity of past dividends. Dalmácio and Corrar (2007) surveyed on management views on corporate dividend policy in Portugal. This paper focuses on the dividend policy of the companies listed on the Lisbon Stock Exchange (LSE), from the viewpoint of their managers.…”
Section: Empirical Evidence Ofmentioning
confidence: 99%
“…Algumas pesquisas evidenciam que diversos fatores institucionais correlacionam-se com as distintas políticas de dividendos (ADJAOUD; BEN-AMAR, 2010; AL SHABIBI; RAMESH, 2011;DALMÁCIO;CORRAR, 2007;FONTELES et al, 2012;HAHN et al, 2010;JIRAPORN;KIM;KIM, 2008;MOTA, 2007;SANTANA, 2005;SROUR, 2005), muitas delas realizadas em economias desenvolvidas, e apresentando resultados divergentes. Diante disso, o presente estudo tem como objetivo geral identificar os principais fatores correlacionados às políticas de dividendos nas empresas do setor elétrico.…”
Section: Introductionunclassified